India-Antarctica-Australia-Laurentia connection in the Paleoproterozoic-Mesoproterozoic revisited: Evidence from new zircon U-Pb and monazite chemical age data from the Eastern Ghats Belt, India - Bose, S.; Dunkley, Daniel; Dasgupta, S.; Das, K.; Arima, M. (Geological Society of America, 2011)
We present zircon and monazite U-Pb data from ultrahigh-temperature (UHT) metamorphosed orthogneisses and paragneisses collected from key areas of the Eastern Ghats Belt, India. The results show contrasting tectonothermal histories in different isotopic domains of the Eastern Ghats Belt that were identified by previous workers. Of particular importance is the discovery of a ca. 1760 Ma event (concordia age) in the southern domain 1A, which is interpreted to be the age of an early UHT metamorphism event. This was followed by a second granulite-facies metamorphism event and partial melting at ca. 1600 Ma. This domain was presumably cratonized with India at around 1600 Ma. The record of the ca. 1760–1600 Ma events in domain 1A of the Eastern Ghats Belt allowsus to speculate on modeling the Paleoproterozoic–Mesoproterozoic transcontinental correlation. The accretionaryorogenic processesin the supercontinent Columbiaen compassed Australia, Antarctica, Laurentia, and parts of India.The central part of Eastern Ghats Belt (isotopic domain 2), on the other hand, contains zircons showing inherited ages of ca.1880–1700 Ma, with a concordant age group of ca. 1760 Ma. Moderately to strongly discordant ages in the time span of ca. 1600–1100 Ma in domain 2 are interpreted to bemixing ages as a result of strong overprint of a ca. 1030–900 Ma tectonothermal event(s) that affected this domain. An early UHT metamorphism event in this domain is inferred to have occurred at ca. 1030–990 Ma (chemical dating of included monazite grains). Zircon records the most pervasive tectonothermal event in this domain at ca. 980–900 Ma, which is correlative with the Rayner orogeny in East Antarctica as a part of the formation of Rodinia.